2014
DOI: 10.1021/jz501761u
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Adsorbate Structures from 1,4-Phenylene Diisocyanide on Gold

Abstract: The structure of the 1-D oligomer chains that form on a Au(111) surface following adsorption of 1,4-phenylene diisocyanide (PDI) is explored using reflection-absorption infrared spectroscopy and scanning tunneling microscopy (STM). The experimental work is complemented by first-principles density functional theory calculations, which indicate that the previously proposed gold-PDI oligomer chains in which the PDI molecule bridged gold adatoms are thermodynamically stable. In addition, the calculated vibrational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(48 citation statements)
references
References 33 publications
3
45
0
Order By: Relevance
“…While these assignments will be discussed in greater detail below, the ~2153 cm -1 peak is assigned to a stretching mode of a goldcoordinated isocyanide and confirms the adsorption of molecular 1,3-PDI on the surface. 28 As the exposure increases, the peak intensities of all of these features decrease, but the peaks also broaden significantly. Heating the sample to ~373 K, a temperature at which any second-layer 1,3-PDI has completely desorbed ( Figure 1(b)), has essentially no effect on the spectrum thereby confirming that the spectra shown in Figure 2 are for 1,3-PDI strongly bound to the surface.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…While these assignments will be discussed in greater detail below, the ~2153 cm -1 peak is assigned to a stretching mode of a goldcoordinated isocyanide and confirms the adsorption of molecular 1,3-PDI on the surface. 28 As the exposure increases, the peak intensities of all of these features decrease, but the peaks also broaden significantly. Heating the sample to ~373 K, a temperature at which any second-layer 1,3-PDI has completely desorbed ( Figure 1(b)), has essentially no effect on the spectrum thereby confirming that the spectra shown in Figure 2 are for 1,3-PDI strongly bound to the surface.…”
Section: Resultsmentioning
confidence: 98%
“…3 This indicates that the self-assembly chemistry of 1,3-PDI on Au(111) is similar to that found for 1,4-PDI, [1][2][3] which forms one-dimensional oligomer chains on the surface comprising repeat -(Au-PDI)units, by extracting gold atoms from lowcoordination sites on the Au(111) substrate. 28 In order to investigate the structural motifs that result in oligomer formation, and to explore the most-stable adsorption sites, the formation of stable species following 1,3-PDI adsorption is investigated using DFT calculations. Note that the calculations did not include van der Waals interactions which have been shown to influence the geometry of 1,4-PDI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The oligomer structure has been confirmed by comparing the results of density functional theory (DFT) calculations with the measured infrared spectra and scanning tunneling microscopy (STM) images collected as a function of tip bias. 24 It is found that the aryl ring of the PDI lies parallel to the surface, but that the molecule is strained such that the isocyanide group is bent by ~12° away from the planar, gas-phase structure. Chain propagation occurs through a mobile, vertical Au-PDI adatom complex that inserts into the terminus of an isocyanide group of PDI bound to a step edge or a surface defect.…”
Section: Introductionmentioning
confidence: 99%
“…The aryl ring is likely to be oriented close to parallel to the surface in the trans oligomer chains, while they may be slightly tilted in the cis elbows and in the hexagonal units (Figure 3), possibly accounting for the additional aryl ring modes detected in the infrared spectra obtained after dosing Au(111) with 1,4-BDT (Figure 2), that are not detected for PDI on Au (111). 59 Evidence for the participation of gold adatoms in the selfassembled structures comes from scanning at different bias voltages. Figure 4d shows chains with alternating intensities with a ∼0.65 nm repeat distance having a dimmer feature between them, while Figure 4c shows hexagons that are ∼0.45 nm across due to flat-lying aryl rings.…”
Section: ■ Resultsmentioning
confidence: 99%